Effect of Various Types of Herbs on Sensory Properties and Blood Glucosa Response Adan Instant Black Rice - Bernatal Saragih; M Marwati; Hadi Suprapto; Bernaulus Saragih; Maulida Rachmawati (International Journal of Science and Engineering, 2013)
Management based on the carbohydrate diet is very important to do and not to be avoided but how diet and variations of carbohydrate consumed is set mainly the source of rice that does not fast respond to an increase in blood glucose. Therefore, Evaluation of nutritional and instant rice production that is the functional food and have a low glycemic index rice sourced locally as the East Kalimantan native rice black Adan will be very beneficial for health. The aim of this research was to evaluate of the nutritional and effect of various herbal on sensory properties and blood glucose response Adan instant black rice. Adan black rice has a protein content of 8.10%, Fe 3.61 mg/1000g and 3.33 g/100g total dietary fiber and includes a group of rice with low amylose. Organoleptic value of instant rice black Adan produced the most preferred by panellists also from the addition of ginger extract and pandan leaves , water, onion tiwai, tea and last turmeric. The digestibility of starch decreased 19.04 (mg/1000g) after being a functional of instant rice black Adan. Difference in reduction of blood glucose levels in volunteers who consumed black Adan instant rice by 14.20 mg/dL, whereas the provision of a reference food (glucose) of 71.50 mg/dL, this indicates of instant rice functional black Adan provide availability of glucose in the blood longer available.